The complexity of governing fishing villages in the bagan areas of Selangor, Malaysia - Mohamed, Mohd Zin; Hassan, Norhaslina (Malaysian Institute of Planners, 2017)
This paper examines the current administrative structure that deals with informal fishing villages in Selangor aiming to identify the governance issues of these communities from the local-, district-, state- and federal-level perspectives. Data collection techniques employed were field observations conducted through site visits, in-depth interviews with the state and local planning officials, and focus group discussions involving chairpersons of the Village Development and Security Committees (VDSC). The analysis reveals a sizable number of entities involved in the governance and management of these fishing communities at all levels and accordingly, concludes by outlining a more strategic administrative structure that could effectively govern informal fishing villages that is applicable to Selangor and beyond.